EKSISTENSI APLIKASI ZOOM SEBAGAI RUANG INOVASI,INTERAKSI, DAN KEHADIRAN RUANG BARU DALAM AKSES PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Muhyi Aditya Supratman; Ardillah Abu (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2022)
The subject matter in this paper discusses 3 basic things in using the Zoom Meeting application. 1). Zoom Meeting as an innovation presented in the context of social change, 2). Zoom Meeting application as a social symbol in the concept of interaction between students and educators, and 3). Zoom Meeting as a concept of dependency and media presence as access to new learning spaces during the Covid-19 pandemic. This study uses literature studies to explain the phenomenon of using the Zoom Meeting application as a new concept that is present in the social reality of educational institutions. The interpretations and explanations obtained by this study are based on e-books and journals related to the online teaching and learning process during the Covid 19 outbreak. Based on the search results through literature analysis and data interpretation, the following study results are obtained; 1). The Zoom Meeting application is an innovative concept presented as a virtual interaction service. Media as a social symbol in use has implications for dynamic societal change. The media as an educational agent places its form of presence as a process of serving human activities in terms of teaching and virtual interaction through the media that has been provided. On this day as a form of social change and the presence of Covid 19 and an effort to minimize the spread, online learning is applied as an alternative to delivering material to be provided in an effort to carry out the educational process. The concept of an innovation space that can frame distance in the Innovation Diffusion perspective places the presence of Zoom Meetings as a media space that can be widely accepted in its context as part of the learning process during the Covid 19 Pandemic. In addition to this, 3). Zoom Meeting is a symbol that presents interaction through a dialogic process when met face-to-face virtually. Furthermore, Zoom Meeting is a medium that is depended on by the community, especially for those who use it as access to information in the new space concept that is present in online learning.